Analisis Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Rumah Makan Mang Engking Di Surakarta - Arifitama, Gilang Hayu, Muzakar Isa, SE, M.Si (2016)
This study aims to investigate the influence of service quality on customer satisfaction at Eating Mang Engking in Surakarta. And to determine the variables that most influence on consumer satisfaction on Eating Mang Engking in Surakarta. The analytical tool used is multiple linear regression, to retrieve data using the method gives the consumer respondents to the questionnaire on Eating Mang Engking in Surakarta. This study refers to the positive approach, the approach that started the study with a hypothesis and then followed by hypothesis testing. From the analysis of each variable can be determined that the variable tangiable, reliability, responsiveness, assurance, and empathy but not significant effect on customer satisfaction on Eating Mang Engking. And the results of the study also showed that variable empathy has the most powerful influence to variable customer satisfaction. This can be seen from the level of probability that most small compared tangiable variables, reliability, responsiveness, and assurance that is equal to 0.179 or 17.9%.